PERLINDUNGAN KONSUMEN PENGGUNA JASA KEUANGAN NON BANK DALAM PERJANJIAN PEMBIAYAAN (CONTOH KASUS: PERUSAHAAN PEMBIAYAAN PT ADIRA FINANCE VS KONSUMEN) - Maria Natasya Shelyn; A.M. Tri Anggraini (Jurnal Hukum Adigama, 2019)
At present, consumers can easily have a vehicle with various waivers such as loans with 0% interest, free administration fees, installments with a small down payment and so forth. However, this causes problems, especially when consumers cant continue installment payments which lead to the forced withdrawal of collateral. The problem that the writer raises is how is the responsibility of non-bank financial service business actors in the example of a financing agreement in PT Adira Finance, what is the form of legal protection for consumers of non-bank financial service users if there’s a loss? What legal remedies can consumers of non-bank financial service users do if there’s a loss? The author examines cases with normative research methods. The data obtained by the author is that the finance company may not withdraw collateral without a confiscation letter and  the third party who seized the collateral must not be arbitrary, must first obtain a certificate from the Professional Certification Institute. Consumers, as stated in the financing agreement of PT Adira Finance, can only settle disputes either by deliberation and consensus or if they are not able to successfully settle in a district court in the creditor's office area or outside the court through the Alternative Dispute Settlement Institution (LAPS) that has been established by OJK. According to the UUPK, the responsibility that can be given by business actors to the detriment of consumers in this case is compensation for money / goods / services worth the price